Recreational Opportunities in Tsarist Russia. Opinion by N.F. Vysotsky: Non-Bacterial Studies of the Kazan Bacteriologist - TRUSHIN, Maxim V. (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.v11.3(51).21, 2021)
At the end of the XIX century in the Russian Empire, the resort business began to develop actively, especially in the Caucasus. This article is devoted to the contribution of the Kazan doctor and bacteriologist Professor Nikolai Fyodorovich Vysotsky to the formation of a new branch of medicine – sanatorium business. The article discusses N.F. Vysotsky's reports on the Caucasian mineral waters and the congress of balneologists. It is shown that N.F. Vysotsky was an outstanding specialist not only in the field of surgery, bacteriology, but also in spa treatment.